Pequenos jogos no futebol: o efeito da utilização de diferentes composições da equipe baseadas no estatuto posicional no desempenho de jovens atletas - Marcelo Vilhena Silva (2017)
This study evaluated the influence of team composition criteria, based on playing position, on tactical, technical, physical behavior and on the network properties of athletes of a soccer team during small-sided games. Twelve athletes belonging to an U-15 team from the south of the country participated in the study. Nine players were distributed into six teams belonging to two groups composed of (a) teams with athletes of the same playing position and (b) by teams with athletes of different playing position. The other three players were part of the Control Group team. In order for these teams to be composed, the study considered the playing position of origin and tactical behavior of the athletes obtained through the System of Tactical Assessment in Soccer. The athletes participated in a small-sided game, held for 4 minutes in the 3vs.3 configuration. Tactical behavior was measured through the evaluation of fundamental tactical principles. The technical behavior was measured by analyzing the technical actions performed. Physical behavior was measured by means of distances, speeds and accelerations. Finally, the interactions among the players were measured through the network analysis. The results of the research indicate that the team composition criteria, based on the positional status, exerted influence on the tactical and technical behavior of the athletes. Physical, physiological and interaction relationships did not change significantly. Regarding tactical behavior, the study showed that the percentage of correctness of offensive, defensive and general tactical principles varied only when the athletes played with colleagues from the same position. The defenders showed a greater percentage of correctness in general and defensive principles, midfielders in offensive principles and forwards in offensive and general principles. The results concerning the incidence of tactical principles found that defenders presented differences in tactical behavior by playing with colleagues from the same position and colleagues from different positions. The midfielders presented differences when playing with colleagues of the same position and the attackers when acting with athletes of different positions. Regarding technical issues, there was a greater number of interceptions and receptions carried out in the field of attack by athletes from different positions. No differences were found in the number of technical actions developed by athletes of the same position. Thus, the study concludes that the composition of the teams, based on positional status only interfered in the athletes' tactical and technical behavior